STRATEGI PEMASARAN DALAM MENINGKATKAN PENDAPATAN USAHA KUE MENURUT PERSPEKTIF EKONOMI ISLAM - Dede Satriani SAM; Evi Avriana (STAIN Bengkalis, 2020)
The marketing strategy is a strategy to serve markets or market segments that are targeted by an entrepreneur.Therefore, the marketing strategy is a combination of marketing mix implemented by entrepreneurs to serve its market.Based on the formulation of the problem, this study aims to determine the marketing strategies of cake entrepreneurs in increasing cake business income.The type of research is empirical, as in this study, researchers describe a situation or phenomenon of the research object studied by developing the concept and collect reality.The research method is descriptive qualitative.From the research results, the marketing strategy applied in increasing the entrepreneur's income is by implementing a marketing mix system; product, price, place and promotion.Viewed from an Islamic economic perspective, cake entrepreneurs also apply the practices of the Prophet Muhammad SAW, namely shiddiq (true and honest), amanah (trustworthy), fathananh (intelligent), and tabligh (communicative).